Genetic diversity and population structure in hair sheep from the Colombian Caribbean Region - Cañas-Alvarez, Jhon Jacobo (2023)
The sheep populations of the Colombian Caribbean Region are characterized by having a high phenotypic heterogeneity mainly due to the use of Creole animals in crossbreeding with exotic breeds. The aim of this study was to estimate the genetic diversity and the population structure of sheep in this region. In total, 459 sheep from 26 farms in 19 municipalities were selected. The DNA samples were genotyped with the ovine low-density chip (15K). Analyses of molecular variance, genetic diversity and population structure were performed. At the phenotypic level, 65.8% of the sampled animals were assigned to the Criollo population, while 15.7% showed signs of introgression with other commercial breeds (mestizos). The populations presented a high degree of genetic diversity within individuals (90.6%) and low levels of genetic variation between populations (FST = 0.075). This low differentiation, together with the low levels of genetic variation between populations, could be attributed to a lack of selection pressure and the existence of gene flow (crossbreeding) between populations.